Wonder Woman [videorecording (DVD)] - Gadot, Gal, 1985-; Pine, Chris, 1980-; Wright, Robin, 1966-; Nielsen, Connie, 1965-; Thewlis, David, 1963-; Marston, William Moulton, 1893-1947 (Warner Bros. Home Entertainment, 2017)
Before she was Wonder Woman she was Diana, princess of the Amazons, trained warrior. When a pilot crashes and tells of conflict in the outside world, she leaves home to fight a war to end all wars, discovering her full powers and true destiny.